(untitled) - Hopper, Leonard J. (Hoboken, N.J., 2005)
This book is the only reference to offer coverage of security design for the site, rather than for the building. It provides landscape architects and other design professionals with the fundamental knowledge they need in order to work with clients and security consultants. It includes guidelines for conducting security/risk assessments as well as case studies that offer a variety of site designs that successfully integrate security.
Keywords: Building sites,Planning,Public buildings,Terrorism,Landscape architecture,Kiến trúc cảnh quan; Security measures; United States,United States